Value chain analysis of Kadaknath chicken in Madhya Pradesh and Chhattisgarh - Amit Tripathy,; D Bardhan,; Sanjay Kumar,; Shiv Kumar,; S R K Singh,; Rizwan Khan,; Chandan Kumar,; D Suryam Dora, (Agricultural Economics Research Review, 2023)
This paper identifies the production and marketing systems of Kadaknath poultry breed by mapping and analyzing the value chains in Madhya Pradesh and Chhattisgarh, the former considered as the cradle of Kadaknath rearing. Qualitative and quantitative data regarding type of chain actors and their interactions were gathered through personal interview method. Farmers/producers, traders, retailers, roadside restaurants/Dhabas and Krishi Vigyan Kendras (KVKs) are the major chain actors involved in identified value chains in the study area. Quantitative mapping reveals that majority (38%) of the birds is sold by farmers to traders and to ultimate consumers at the farm gate (33%).About 39% of the birds procured by traders are exported to other districts, while 31% and 22% of the birds are sold by traders to road side Dhabas and ultimate consumers, respectively. Of the total value added, traders in fresh/raw chicken chains and restaurants/Dhabas in value added chains capture significant shares. Some policy suggestions have been made to streamline the Kadaknath value chains towards integrated and inclusive production and marketing systems so as to benefit resource-poor farmers in the study area.